2017
DOI: 10.1038/cdd.2017.153
|View full text |Cite
|
Sign up to set email alerts
|

A vitronectin-derived peptide reverses ovariectomy-induced bone loss via regulation of osteoblast and osteoclast differentiation

Abstract: Osteoporosis affects millions of people worldwide by promoting bone resorption and impairing bone formation. Bisphosphonates, commonly used agents to treat osteoporosis, cannot reverse the substantial bone loss that has already occurred by the time of diagnosis. Moreover, their undesirable side-effects, including osteonecrosis of the jaw, have been reported. Here, we demonstrated that a new bioactive core vitronectin-derived peptide (VnP-16) promoted bone formation by accelerating osteoblast differentiation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 58 publications
1
75
0
Order By: Relevance
“…NFATC1 regulates the expression of numerous osteoclasogenic genes, and it has been reported that embryonic stem cells with NFATC1-genetic deficiency cannot differentiate into mature osteoclasts 41 . c-Src influences bone absorption through mediating the adhesion and migration of osteoclasts 42 . CTSK and MMP-9 involve in the degradation of bone matrix and then induce the activation of bone-resorptive 43 .…”
Section: Discussionmentioning
confidence: 99%
“…NFATC1 regulates the expression of numerous osteoclasogenic genes, and it has been reported that embryonic stem cells with NFATC1-genetic deficiency cannot differentiate into mature osteoclasts 41 . c-Src influences bone absorption through mediating the adhesion and migration of osteoclasts 42 . CTSK and MMP-9 involve in the degradation of bone matrix and then induce the activation of bone-resorptive 43 .…”
Section: Discussionmentioning
confidence: 99%
“…There have been attempts to develop anti-osteoporosis agents without side-effects. In recent years, several BAPs with a potential anti-osteoporotic effect have been developed from various endogenous proteins [ 12 , 17 , 18 ]. In addition, BAPs that could stimulate osteoblast differentiation and showed an anti-osteoporotic effect have also been developed from food proteins by enzymatic hydrolysis [ 10 , 11 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism behind the superior bone cell responses has been tried to be explained, based on the hypothesized tunable allosteric control of the receptor proteins [67,70]. A recent investigation evaluating a functional peptide from vitronectin found a Janus effect of this peptide for bone formation, activating osteoblasts and inhibiting osteoclasts, that is, controlling the osteoporotic environment locally to be favorable for osseointegration [71].…”
Section: Functional Peptidesmentioning
confidence: 99%